PRACTICAL ASPECTS OF FORMING THE SPIRITUAL AND EDUCATIONAL CHARACTER OF PRESCHOOL CHILDREN - Niyozova Maftuna Normaxmat qizi (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the practical aspects of forming the spiritual and educational character of preschool children. Preschool age is an important stage during which the foundations of a child’s worldview, moral consciousness, behavioural culture, national identity, emotional responsiveness, and attitude towards other people are developed. Spiritual and educational development is not limited to teaching children certain rules or providing information about national traditions. It is a continuous pedagogical process based on personal example, meaningful communication, play, literature, art, family traditions, social experience, and the organisation of a morally supportive educational environment. The article analyses the role of the family, preschool educational organisation, teacher, peer group, national values, folklore, artistic activities, nature, and modern pedagogical technologies in this process. Particular attention is paid to moral conversations, role-playing games, problem-based situations, fairy tales, collaborative activities, cultural events, family projects, and reflective methods.